Provable secure proxy signature scheme without bilinear pairings. (16th November 2011) - Tiwari, Namita; Padhye, Sahadeo
SUMMARY Proxy signature is an active research area in cryptography. A proxy signature scheme allows an entity to delegate his or her signing capability to another entity in such a way that the latter can sign messages on behalf of the former. Many proxy signature schemes using bilinear pairings have been proposed. But the relative computation cost of the pairing is more than 10 times of the scalar multiplication over elliptic curve group. In order to save the running time and the size of the signature, we propose a proxy signature scheme without bilinear pairings and prove its security against adaptive chosen‐message attack in random oracle model. The security of our scheme is based on the hardness of the elliptic curve discrete logarithm problem. With the running time being saved greatly, our scheme is more practical than the previous related scheme for practical applications. Copyright © 2011 John Wiley & Sons, Ltd.